Audit Committee Incentive Compensation and Accounting Restatements* - Archambeault, Deborah S.; Dezoort, F. Todd; Hermanson, Dana R. (Contemporary Accounting Research, 2008)
This study investigates whether incentive-based compensation for audit committee members is associated with accounting restatements. We use an agency framework to predict that short-term (long-term) incentive compensation for audit committee members will increase (decrease) the likelihood of accounting restatements due to error or fraud. Using a matched-sample logistic regression with 153 restatement and 153 nonrestatement companies, we find the predicted positive relation between short-term incentive compensation (short-term stock option grants) for audit committee members and likelihood of restatement. However, the long-term incentive compensation results contradict prediction and indicate a significant positive relation between audit committee member long-term incentive compensation {long-term stock option grants) and restatement likelihood. Supplemental testing provides evidence that the findings generally are robust to numerous alternative measures and models. The results raise questions about stock option grants for audit committee members and suggest the need for additional theoretical and empirical research to clarify the audit committee's role and incentives in agency frameworks.,